Lisbon Binding Workshop - Workshop on Binding Theory and Invariants in Anaphoric Relations (hosted by HPSG'2005): Workshop Notes - Branco, António Horta (2009)
This technical report collects the extended abstracts selected for the Workshop on Binding Theory and Invariants in Anaphoric Relations, hosted by the HPSG'2005 Conference (University of Lisbon, August 22, 2005 - http://bindingwksp.di.fc.ul.pt/) by the corresponding program committee